The Potential Of Fungi And Bacteria As α-Glucosidase Inhibitors For The Future Treatment Of Type 2 Diabetes - Edy Fachrial; Ismawati; Afif P Jati; Titania T Nugroho; Saryono (Jurnal Penelitian Pendidikan IPA, 2025)
Diabetes, a disorder of hemostasis of carbohydrate and lipid metabolism, is one of today's leading killers. The most prevalent form of diabetes is type 2 diabetes mellitus (T2DM). Rapid hydrolysis of starch by pancreatic α-amylase and α-glucosidase, followed by intestinal absorption of glucose, causes a sudden increase in blood glucose. Available therapies for T2DM are oral insulin secretagogues, sulfonylureas, repaglinide, nateglinide, biguanides, thiazolidinediones, α-glucosidase, inhibitors and insulin. However, several hypoglycemic agents have limitations, such as side effects and increased diabetes complications. α-glucosidase inhibitors are structurally similar to natural oligosaccharides with a higher affinity for α-glucosidases, and they produce a reversible inhibition of membrane-bound intestinal α-glucoside hydrolase enzymes. This causes delayed carbohydrate absorption and digestion and results in a reduction in postprandial hyperglycemia. Natural α-glucosidase inhibitor drugs from natural sources can be used as a therapeutic approach to treat postprandial hyperglycemia for their assumed lower side effect and more affordable price than synthetic drugs. In this article, the author summarizes the potential of α-glucosidase inhibitors from microorganisms, namely fungi and bacteria, along with several active compounds with better activity than commercial α-glucosidase inhibitors.